EU competitiveness at a crossroads: Why the Draghi Report falls short, and the EU treaties offer a solution - Thomas Weck (EconPol Forum, 2024)
The EU Treaties rely on an open market economy - the Draghi Report does not. The EU's lag in cutting-edge tech is known, and Draghi's state-driven response is unconvincing. EU overregulation is an issue particularly in the strategic areas identified by Draghi. Large-scale public funding distorts markets and burdens the population. The Draghi Report advocates reducing dependencies, but lacks global trade strategy.
Keywords: 330